Pelatihan Manajemen Database dan Website Bootstrap untuk Digitalisasi Administrasi Jemaat GKPS Maranatha - Elwin Yunith Purba; Andreas Jorghy Parapat; Saferius Harefa (CV. Devi Tara Innovations, 2026)
Effective congregational data management and information dissemination have become essential components in supporting church administration and ministry in the digital era. However, many churches continue to encounter challenges in managing congregational databases and utilizing information technology, particularly in the development of web-based information systems. To address these challenges, a Community Service Program (PKM) entitled